PHENYL ALANINE AMMONIA LYASE (PAL) ACTIVITY AND ARTEMISININ CONTENTS OF ARTEMISIA ANNUA L., DURING CALLUS GROWTH - S. JHANSI RANI,; A. VASAVI,; P. SUPRAJA,; R. USHA, (The Bioscan, 2012)
The relationship between the level of phenyl alanine ammonia lyase and the concentration of artemisinin produced in the callus cultures of Artemisia annua. L was studied. TLC and high performance liquid chromatographic analysis indicated the presence of maximum artemisinin production was associated with the higher level of PAL activity at the 4th week of callus growth. Both artemisinin and level of enzyme activity declined subsequently by 5th week. Protein and nucleic acid contents of the callus during the growth showed an inverse relationship with the level of phenyl alanine ammonia lyase. The enzyme appears to play a cardinal role in the production of artemisinin during the callus growth.